NiCr-Cr3C2 / WC-10Co4Cr composite coating reinforced heavy load automobile wheel hub

CN122979804APending Publication Date: 2026-10-27JINAN TIANMENG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611302843.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-26
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

仅喷涂单层厚 NiCr-Cr3C2 涂层:材料成本低、附着力好,但耐磨、抗冲蚀性能弱于WC-10Co4Cr,无法满足矿山、长途重载高强度磨损工况;

Benefits of technology

(1)无镍铝复合涂层综合性能均衡稳定 10 丝NiCr-Cr3C2或Cr3C2@NiCr-Mo-La2O3-TiC过渡层兼具热应力缓冲、耐磨、防腐多重功能,替代功能单一的镍铝底层;双层含铬体系形成双重钝化防护,面层 3~5 丝WC-10Co4Cr提供核心耐磨抗冲蚀能力;整套复合涂层性能优于单层 NiCr-Cr3C2或Cr3C2@NiCr-Mo-La2O3-TiC,适配绝大多数重载运输工况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979804A_ABST
    Figure CN122979804A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of coating, and relates to a NiCr-Cr3C2 / WC-10Co4Cr composite coating reinforced heavy load automobile hub, comprising: a heavy load automobile hub; the heavy load automobile hub is loaded with a multifunctional transition layer on the surface; the multifunctional transition layer is loaded with a surface layer; the material of the multifunctional transition layer is NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC; the material of the surface layer is WC-10Co4Cr. The present application completely abandons the nickel aluminum layer, and adopts the functional NiCr-Cr3C2 / Cr3C2@NiCr-Mo-La2O3-TiC instead, which takes into account the multiple effects of transition layer buffering, wear resistance and corrosion resistance; and the present application forms a composite structure with the WC-10Co4Cr surface layer; effectively taking into account the requirements of thermal stress, impact wear resistance and corrosion resistance, and at the same time, the material cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coatings, specifically relating to a heavy-duty automobile wheel hub reinforced with a NiCr-Cr3C2 / WC-10Co4Cr composite coating. Background Technology

[0002] Heavy-duty trucks, mining dump trucks, and long-haul semi-trailer tractors operate on gravel roads, in winter under conditions of snow-melting salt, and in muddy, acidic, and alkaline conditions. The wheel hubs, flanges, and friction surfaces are constantly subjected to gravel erosion, high braking temperatures, and electrochemical corrosion. Existing surface strengthening solutions have the following drawbacks: Conventional electrophoresis, galvanizing, and hard anodizing provide single-layer protection with low hardness, resulting in scratches, pits, and rust appearing in the friction area in a short period of time, leading to rapid wheel hub failure and high replacement and maintenance costs. Directly spraying a single layer of WC-10Co4Cr coating onto the surface of the wheel hub substrate: The thermal expansion coefficients of the metal substrate and the tungsten carbide coating are very different. After continuous braking and hot and cold cycles on a long downhill slope, the coating is prone to cracking, peeling, and peeling off in pieces. If the WC-10Co4Cr coating is thickened to improve adhesion, the amount of expensive powder used will increase significantly, and the cost per unit will increase significantly. Spraying only a single layer of thick NiCr-Cr3C2 coating: low material cost and good adhesion, but the wear resistance and erosion resistance are weaker than WC-10Co4Cr, which cannot meet the requirements of mining, long-distance heavy load and high-intensity wear conditions. Existing composite coating solutions mostly use nickel-aluminum as a transition layer. However, existing nickel-aluminum coatings have low wear resistance and corrosion resistance, and their functions are limited, making it difficult to simultaneously meet the requirements for thermal stress, impact wear resistance, and corrosion resistance. Summary of the Invention

[0003] To address the aforementioned problems, this invention provides a heavy-duty automotive wheel hub reinforced with a NiCr-Cr3C2 / WC-10Co4Cr composite coating. This invention completely eliminates the nickel-aluminum layer, replacing it with a functional NiCr-Cr3C2 / Cr3C2@NiCr-Mo-La2O3-TiC layer, thus combining the multiple functions of a transition layer—buffering, wear resistance, and corrosion protection. Together with the WC-10Co4Cr surface layer, it forms a composite structure. The NiCr-Cr3C2 itself exhibits superior performance compared to the wheel hub substrate, buffering thermal stress, sharing impact wear, and providing auxiliary corrosion protection. The surface layer ensures core wear resistance and corrosion protection, effectively addressing the requirements of thermal stress, impact wear resistance, and corrosion protection, while significantly reducing material costs.

[0004] To achieve the above technical objectives, the present invention adopts the following technical solution: A first aspect of the present invention provides a heavy-duty vehicle wheel hub reinforced with a NiCr-Cr3C2 / WC-10Co4Cr composite coating, comprising: Heavy-duty car wheel hubs; The heavy-duty vehicle wheel hub surface has a multi-functional transition layer; The multifunctional transition layer is loaded with a surface layer; The material of the multifunctional transition layer is NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC; The surface layer is made of WC-10Co4Cr.

[0005] The composite coating of this invention has better hardness, wear resistance, and salt spray corrosion resistance than the metal substrate of the wheel hub. On the one hand, it reduces the difference in thermal expansion between the substrate and the WC surface layer, buffers the thermal stress generated by high braking temperature, and prevents the surface layer from cracking and falling off. On the other hand, it can independently withstand light sand and gravel impact and salt spray corrosion, sharing the load of the surface layer. Moreover, the purchase price of NiCr-Cr3C2 is much lower than that of WC-10Co4Cr, and the use of thick layers will not significantly increase the cost.

[0006] The surface layer relies on the WC hard phase to resist high-intensity friction and gravel erosion, while the cobalt-chromium binder phase in the coating forms a dense passivation film that blocks the penetration of snow-melting salt, acid and alkali mud water; only a thin layer is sprayed, which greatly reduces the consumption of expensive tungsten carbide powder; it can meet the needs of most heavy-duty vehicles on highways, construction sites, and roads where salt is spread in winter.

[0007] In a second aspect, the present invention provides a heavy-duty vehicle wheel hub prepared by the method described above.

[0008] A third aspect of the present invention provides the application of the above-mentioned NiCr-Cr3C2 / WC-10Co4Cr composite coating or Cr3C2@NiCr-Mo-La2O3-TiC / WC-10Co4Cr composite coating in the preparation of industrial heavy-duty casters, logistics equipment, engineering machinery and agricultural machinery.

[0009] The beneficial effects of this invention are as follows: (1) The nickel-free aluminum composite coating has a balanced and stable comprehensive performance. The 10-wire NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC transition layer has multiple functions such as thermal stress buffering, wear resistance and corrosion protection, replacing the single-function nickel-aluminum underlayer. The double-layer chromium-containing system forms double passivation protection, and the 3-5 wire WC-10Co4Cr surface layer provides core wear resistance and erosion resistance. The performance of the entire composite coating is better than that of single-layer NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC, and it is suitable for most heavy-duty transportation conditions.

[0010] (2) Excellent corrosion resistance: Both NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC and WC-10Co4Cr double layers can generate chromium oxide passivation film, which double blocks the penetration of chloride ions and acid and alkali media. The neutral salt spray test can reach more than 1000 hours without pitting corrosion, which is far superior to ordinary electrophoresis and zinc plating protective layers.

[0011] (3) Significant cost advantage: The thick layer uses low-cost NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC, while only the thin layer uses high-cost tungsten carbide powder. Compared with the single-layer thickened WC-10Co4Cr scheme, the total cost of ceramic powder is significantly reduced. In the Cr3C2@NiCr-Mo-La2O3-TiC layer, Cr3C2 is the core and NiCr-Mo-La2O3-TiC is the outer shell. La2O3 can act as a heterogeneous nucleation core, refine the coarse NiCr and Mo solid solution alloy grains, improve the interfacial wettability between the NiCr-Mo alloy phase and the Cr3C2 core, and make the NiCr-Mo alloy phase shell completely cover the Cr3C2 particles, significantly improving the buffering performance and corrosion resistance of the transition layer. The overall thermal stress and impact wear damage of the composite coating are significantly reduced.

[0012] (4) The maintenance cost of the wheel hub throughout its entire life cycle is reduced. The core high wear and corrosion area is reinforced with a double-layer composite, which greatly reduces the frequency of wheel hub replacement and on-site grinding and recoating for the fleet, and reduces the maintenance cost in the later stage.

[0013] (5) Environmental advantages: It can replace the high-pollution hard chromium plating process and has no hexavalent chromium pollutants; the spray powder can be recycled and reused, reducing solid waste emissions. Attached Figure Description

[0014] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0015] Figure 1 The image shows a heavy-duty automobile wheel hub after applying a composite coating, as shown in Embodiment 4 of the present invention. Detailed Implementation

[0016] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0017] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0018] As described in the background section, existing nickel-aluminum coatings have low wear resistance and corrosion resistance, and their functions are limited, making it difficult to simultaneously meet the requirements for thermal stress resistance, impact wear resistance, and corrosion resistance. Therefore, this invention provides a heavy-duty automotive wheel hub reinforced with a NiCr-Cr3C2 / WC-10Co4Cr composite coating, comprising: Heavy-duty car wheel hubs; The heavy-duty vehicle wheel hub surface has a multi-functional transition layer; The multifunctional transition layer is loaded with a surface layer; The material of the multifunctional transition layer is NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC; The surface layer is made of WC-10Co4Cr.

[0019] This invention uses Cr3C2 as the core and NiCr-Mo-La2O3-TiC as the outer shell. The core-shell structure effectively improves the buffering performance and corrosion resistance of the coating. Mo regulates thermal stress, La2O3 refines grains to reduce porosity, and TiC whiskers toughen the coating. During the melting stage, La has high activity and preferentially captures O and S impurities in the molten pool to form high-melting-point rare earth composite salts, eliminating brittle inclusions and preventing impurity points from becoming stress concentration sources. This allows the effect of Mo in regulating thermal expansion to be fully realized. In particular, La2O3 can act as a heterogeneous nucleation core, refining the coarse NiCr and Mo solid solution alloy grains, improving the interfacial wettability between the NiCr-Mo alloy phase and the Cr3C2 core, and ensuring that the NiCr-Mo alloy phase shell completely covers the Cr3C2 particles. This significantly improves the buffering performance and corrosion resistance of the transition layer, and significantly reduces the overall thermal stress and impact wear damage of the composite coating.

[0020] Compared with the substrate and the surface layer, the multifunctional transition layer has a moderate coefficient of thermal expansion, which can effectively reduce the impact of thermal stress and improve corrosion resistance. Therefore, this invention studies the coating thickness of the multifunctional transition layer. Preferably, the coating thickness of the multifunctional transition layer is 10-12 mils to obtain better corrosion resistance.

[0021] The surface layer has functions such as wear resistance, impact resistance, and corrosion resistance. However, it is also relatively expensive. Therefore, this invention studies the thickness of the surface layer. Preferably, the coating thickness of the surface layer is 3 to 5 microns, so as to reduce the coating thickness while ensuring wear resistance, impact resistance, and corrosion resistance.

[0022] The amount of each component in Cr3C2@NiCr-Mo-La2O3-TiC affects the performance of the transition layer. Therefore, this invention has studied the amount of each component. Preferably, the Cr3C2@NiCr-Mo-La2O3-TiC is composed of the following raw materials in weight percentages: Cr3C2: 68%–75%, NiCr: 22%–28%, Mo: 0.8%–2.5%, La2O3: 0.3%–1.2%, and TiC: 0.2%–0.8%, to obtain better buffering and corrosion resistance properties.

[0023] This invention does not impose any particular limitation on the preparation method of Cr3C2@NiCr-Mo-La2O3-TiC. Preferably, the preparation method of Cr3C2@NiCr-Mo-La2O3-TiC includes: Cr3C2 was activated using a silane coupling agent; The activated Cr3C2, Ni, Cr, Mo, La2O3 and TiC are mixed, wet ball milled, spray granulated and vacuum sintered to obtain the Cr3C2@NiCr-Mo-La2O3-TiC coating, which simplifies the preparation process and improves the performance of the coating.

[0024] The ball-to-material ratio, rotation speed, and time in wet ball milling affect grinding efficiency, particle size distribution, and product dispersibility. Therefore, this invention studies the ball-to-material ratio, rotation speed, and time in wet ball milling. Preferably, the ball milling speed is 350-400 r / min, the milling time is 4-6 h, and the ball-to-material ratio is 8-10:1 to obtain better dispersion effect.

[0025] Vacuum sintering temperature affects the density, microstructure and final properties of materials. Therefore, this invention has studied the vacuum sintering temperature and time. Preferably, the vacuum sintering is carried out under inert gas protection, and the temperature is raised to 950-1050℃ and held for 30-40 minutes to obtain better product performance.

[0026] Preferably, the transition layer and the top layer are applied using supersonic flame spraying. Supersonic flame spraying relies on high-speed, low-temperature deposition, low oxidation, high density, high bonding strength, and coating compressive stress characteristics. It can protect the WC powder from decarburization, fully retain the functions of all modified additives, and stably prepare a 10–12 mil thick transition layer and a 3–5 mil ultrathin top layer. The dual-layer interface has a strong bond, excellent corrosion resistance and wear resistance, and is suitable for mass production of wheel hub partitioned spraying, perfectly matching the harsh working conditions of heavy-duty wheel hubs under alternating hot and cold temperatures, sand and gravel erosion, and salt spray corrosion.

[0027] The present invention will be further described in detail below with reference to specific embodiments. It should be noted that the specific embodiments are explanations of the present invention and not limitations thereof.

[0028] In the following examples and comparative examples, the preparation method of Cr3C2@NiCr-Mo-La2O3-TiC includes: Formula: 272 parts Cr3C, 25 parts NiCr alloy (20 parts Ni, 5 parts Cr), 1.8 parts Mo, 0.7 parts La2O3, 0.5 parts nano TiC whiskers, total 100 parts.

[0029] 1) Silane activation treatment of Cr3C2 particles: Silane coupling agent KH550 concentration 1.2wt%, soaked in ethanol solution and stirred for 30min, dried at 80℃ to obtain activated Cr3C2; 2) Wet coating ball milling: Activated Cr3C2 powder with Ni, Cr, Mo, La2O3 and TiC powder, anhydrous ethanol medium, ball-to-material ratio 10:1, ball milling speed 350 r / min, ball milling time 6 h; 3) Spray granulation: The slurry has a solid content of 42%. An imported centrifugal spray dryer is used with an inlet air temperature of 190°C and an outlet air temperature of 85°C to obtain spherical agglomerated intermediates. 4) Low-temperature vacuum pre-alloying: vacuum degree 8×10 -3 Pa, under argon protection, heat to 950℃ and hold for 40 minutes, then cool with the furnace; 5) Airflow classification and sieving to extract 15-45μm powder for later use.

[0030] Example 1 Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of NiCr-Cr3C2 transition reinforcement layer powder, coating thickness is 10 mil; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (3) Supersonic flame spraying of WC-10Co4Cr wear-resistant and corrosion-resistant surface layer. WC-10Co4Cr surface layer is sprayed on the NiCr-Cr3C2 transition layer with a thickness of 4 mil (inland mining site); kerosene flow rate 22L / h, oxygen flow rate 880L / min; nitrogen powder feeding pressure 0.4MPa, powder feeding rate 32g / min; spray gun moving speed 420mm / s, spraying distance 190mm; single spray thickness 0.4 mil.

[0031] (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, spray a high-temperature resistant silicone sealant (commercially available thermal spray sealant) with an ambient humidity of ≤70% using low-pressure air spraying. The dry film thickness of the sealant is 8-12 μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, allow it to stand at room temperature for 2 hours to pre-dry, and then bake it at 160°C for 1.5 hours to cure.

[0032] Example 2 Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of NiCr-Cr3C2 transition reinforcement layer powder, coating thickness is 10 mil; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (3) Supersonic flame spraying of WC-10Co4Cr wear-resistant and corrosion-resistant surface layer. WC-10Co4Cr surface layer is sprayed on the NiCr-Cr3C2 transition layer with a thickness of 3 mil (dry inland highway); kerosene flow rate is 22L / h, oxygen flow rate is 880L / min; nitrogen powder feeding pressure is 0.4MPa, powder feeding rate is 32g / min; spray gun moving speed is 420mm / s, spraying distance is 190mm; single spray thickness is 0.4 mil.

[0033] (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, a high-temperature resistant silicone sealant is sprayed on. The ambient humidity is ≤70%, and the spraying is done with low-pressure air. The dry film thickness of the sealant is 8-12μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, the workpiece is left to stand at room temperature for 2 hours to pre-dry, and then baked at 160°C for 1.5 hours to cure.

[0034] Example 3 Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of NiCr-Cr3C2 transition reinforcement layer powder, coating thickness is 10 mil; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (3) Supersonic flame spraying of WC-10Co4Cr wear-resistant and corrosion-resistant surface layer. WC-10Co4Cr surface layer is sprayed on the NiCr-Cr3C2 transition layer with a thickness of 5 mil (coastal / long-term salting section in winter); kerosene flow rate 22L / h, oxygen flow rate 880L / min; nitrogen powder feeding pressure 0.4MPa, powder feeding rate 32g / min; spray gun moving speed 420mm / s, spraying distance 190mm; single spray thickness 0.4 mil.

[0035] (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, a high-temperature resistant silicone sealant is sprayed on. The ambient humidity is ≤70%, and the spraying is done with low-pressure air. The dry film thickness of the sealant is 8-12μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, the workpiece is left to stand at room temperature for 2 hours to pre-dry, and then baked at 160°C for 1.5 hours to cure.

[0036] Example 4 Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of Cr3C2@NiCr-Mo-La2O3-TiC transition reinforcement layer powder, with a coating thickness of 10 mils; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (3) Supersonic flame spraying of WC-10Co4Cr wear-resistant and corrosion-resistant surface layer. WC-10Co4Cr surface layer with a thickness of 4 mil was sprayed on the surface of Cr3C2@NiCr-Mo-La2O3-TiC transition layer; kerosene flow rate 22L / h, oxygen flow rate 880L / min; nitrogen powder feeding pressure 0.4MPa, powder feeding rate 32g / min; spray gun moving speed 420mm / s, spraying distance 190mm; single spray thickness 0.4 mil.

[0037] (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, a high-temperature resistant silicone sealant is sprayed on. The ambient humidity is ≤70%, and the spraying is done with low-pressure air. The dry film thickness of the sealant is 8-12μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, the workpiece is left to stand at room temperature for 2 hours to pre-dry, and then baked at 160°C for 1.5 hours to cure.

[0038] Comparative Example 1: Low-cost simplified solution for single-layer NiCr-Cr3C2 (urban light-duty trailer) Only a 10-micron NiCr-Cr3C2 single-layer coating is sprayed, omitting the WC-10Co4Cr topcoat. Specifically, it includes: Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of NiCr-Cr3C2 transition reinforcement layer powder, coating thickness is 10 mil; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, a high-temperature resistant silicone sealant is sprayed on. The ambient humidity is ≤70%, and the spraying is done with low-pressure air. The dry film thickness of the sealant is 8-12μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, the workpiece is left to stand at room temperature for 2 hours to pre-dry, and then baked at 160°C for 1.5 hours to cure.

[0039] Comparative Example 2: Monolayer Cr3C2@NiCr-Mo-La2O3-TiC scheme Only a 10-filament Cr3C2@NiCr-Mo-La2O3-TiC single-layer coating is applied, omitting the WC-10Co4Cr topcoat. Specifically, this includes: Wheel hub base: Heavy-duty cast steel (1) Pre-treatment of workpieces: White corundum is used for sandblasting in the spraying area, and no sandblasting is used in the non-spraying area to reduce the energy consumption of sand and air compressor; (2) Supersonic flame spraying of Cr3C2@NiCr-Mo-La2O3-TiC transition reinforcement layer powder, with a coating thickness of 10 mils; combustion medium parameters: kerosene flow rate 24L / h, high-purity oxygen flow rate 920L / min; powder feeding system: carrier gas is high-purity nitrogen, powder feeding pressure 0.42MPa, powder feeding rate 38g / min; spraying motion parameters: spray gun moving speed 450mm / s, spraying distance 200mm; (4) Low-temperature sealing post-treatment: After the workpiece is cooled to 40°C, a high-temperature resistant silicone sealant is sprayed on. The ambient humidity is ≤70%, and the spraying is done with low-pressure air. The dry film thickness of the sealant is 8-12μm, which seals the micropores inside the composite coating and provides secondary protection against corrosive media from penetrating the substrate. Finally, the workpiece is left to stand at room temperature for 2 hours to pre-dry, and then baked at 160°C for 1.5 hours to cure.

[0040] Comparative Example 3: The difference from Example 4 is that La2O3 was not added. Specifically, it includes: Formula: 272 parts Cr3C, 25 parts NiCr alloy (20 parts Ni, 5 parts Cr), 1.8 parts Mo, 0.5 parts nano TiC whiskers, total 100 parts.

[0041] 1) Silane activation treatment of Cr3C2 particles: Silane coupling agent KH550 concentration 1.2wt%, soaked in ethanol solution and stirred for 30min, dried at 80℃ to obtain activated Cr3C2; 2) Wet coating ball milling: Activated Cr3C2 and Ni, Cr, Mo and TiC powders, anhydrous ethanol medium, ball-to-material ratio 10:1, ball milling speed 350 r / min, ball milling time 6 h; 3) Spray granulation: The slurry has a solid content of 42%. An imported centrifugal spray dryer is used with an inlet air temperature of 190°C and an outlet air temperature of 85°C to obtain spherical agglomerated intermediates. 4) Low-temperature vacuum pre-alloying: vacuum degree 8×10 -3 Pa, under argon protection, heat to 950℃ and hold for 40 minutes, then cool with the furnace; 5) Airflow classification and sieving to extract 15-45μm powder for later use.

[0042] The substrate and spraying process are the same as in Example 4.

[0043] Comparative Example 4: The difference from Example 4 is that an equal mass of Y₂O₃ is used instead of La₂O₃. Specifically, this includes: Formula: 272 parts Cr3C, 25 parts NiCr alloy (20 parts Ni, 5 parts Cr), 1.8 parts Mo, 0.7 parts Y2O3, 0.5 parts nano TiC whiskers, total 100 parts.

[0044] 1) Silane activation treatment of Cr3C2 particles: Silane coupling agent KH550 concentration 1.2wt%, soaked in ethanol solution and stirred for 30min, dried at 80℃ to obtain activated Cr3C2; 2) Wet coating ball milling: Activated Cr3C2 powder with Ni, Cr, Mo, Y2O3 and TiC powder, anhydrous ethanol medium, ball-to-material ratio 10:1, ball milling speed 350 r / min, ball milling time 6 h; 3) Spray granulation: The slurry has a solid content of 42%. An imported centrifugal spray dryer is used with an inlet air temperature of 190°C and an outlet air temperature of 85°C to obtain spherical agglomerated intermediates. 4) Low-temperature vacuum pre-alloying: vacuum degree 8×10 -3 Pa, under argon protection, heat to 950℃ and hold for 40 minutes, then cool with the furnace; 5) Airflow classification and sieving to extract 15-45μm powder for later use.

[0045] The substrate and spraying process are the same as in Example 4.

[0046] Comparative Example 5: The difference from Example 4 is that an equal mass of CeO2 is used instead of La2O3. Specifically, this includes: Formula: 272 parts Cr3C, 25 parts NiCr alloy (20 parts Ni, 5 parts Cr), 1.8 parts Mo, 0.7 parts CeO, 0.5 parts nano TiC whiskers, total 100 parts.

[0047] 1) Silane activation treatment of Cr3C2 particles: Silane coupling agent KH550 concentration 1.2wt%, soaked in ethanol solution and stirred for 30min, dried at 80℃ to obtain activated Cr3C2; 2) Wet coating ball milling: Activated Cr3C2 and Ni, Cr, Mo, CeO2 and TiC powders, anhydrous ethanol medium, ball-to-material ratio 10:1, ball milling speed 350 r / min, ball milling time 6 h; 3) Spray granulation: The slurry has a solid content of 42%. An imported centrifugal spray dryer is used with an inlet air temperature of 190°C and an outlet air temperature of 85°C to obtain spherical agglomerated intermediates. 4) Low-temperature vacuum pre-alloying: vacuum degree 8×10 -3 Pa, under argon protection, heat to 950℃ and hold for 40 minutes, then cool with the furnace; 5) Airflow classification and sieving to extract 15-45μm powder for later use.

[0048] Experimental example: I. Thermal stress and thermal cycling stability test Testing equipment: Programmable box-type high-temperature circulating heat treatment furnace, equipped with a high-precision coating residual stress detector (X-ray diffraction stress method). Uniform sample specifications: taken from the sprayed area of ​​the rim of heavy-duty cast steel wheel hub, sample size 50mm×30mm, completely retaining the 10-mil transition layer / 3~5-mil surface layer composite coating structure. Thermal cycling parameters: Heating phase: Heating rate 8℃ / min, from room temperature 25℃ to 550℃; High temperature insulation: 550℃ constant temperature for 15 minutes to simulate the high temperature condition of continuous vehicle braking; Cooling stage: Natural cooling inside the furnace, cooling rate 6℃ / min, cooling down to room temperature 25℃ is one cycle; Total number of cycles: 1000 consecutive high and low temperature alternation cycles; Detection and judgment: (1) Residual thermal stress test: Before the thermal cycling test, the residual thermal stress at the interface between the coating and the substrate was detected by X-ray diffraction. The unit is MPa. The compressive stress is recorded as a negative value and the tensile stress is recorded as a positive value. The smaller the absolute value, the better the thermal matching. (2) Observation of coating appearance: Take out the sample every 200 cycles and observe the coating surface and side cross section with an optical microscope (200×). Record whether microcracks, through cracks, local edge warping, interlayer delamination, or peeling and flaking occur. Take a metallographic image of the cross section after 1000 cycles.

[0049] II. Sand and gravel erosion and impact wear test Testing equipment: High-pressure gas erosion and wear tester; Erosion medium: 40-mesh pure quartz sand, hardness 900HV, free of dust and lumps, simulating the impact conditions of mining sand and gravel. Test parameters: The sandblasting pressure was 0.5 MPa, the abrasive impact angle was 75°, the nozzle distance from the sample surface was 150 mm, and the total amount of abrasive used in a single erosion was 100 g. Sample pretreatment: Before testing, place the sample in a 100℃ oven to dry for 30 minutes, cool it to room temperature, weigh it using an electronic balance with an accuracy of 0.01%, and record the initial mass. Calculation method: After erosion is completed, blow away the residual sand and dust on the surface, dry and weigh it, and calculate the coating wear amount corresponding to the unit sand material. Wear amount = (initial mass - mass after erosion) / total mass of eroded sand, unit mg / g; the smaller the value, the better the resistance to sand and gravel erosion and impact resistance.

[0050] III. Neutral Salt Spray (NSS) Corrosion Resistance Test Implementation standard: GB / T10125-2021 Artificial atmosphere corrosion test - salt spray test; Testing equipment: Fully automatic neutral salt spray test chamber; Salt spray solution preparation: 5% sodium chloride aqueous solution, pH value controlled at 6.5~7.2; Chamber environment: The test temperature was kept constant at 35℃, and the salt spray deposition rate was 1.0~2.0 mL / (80cm). 2 •h); Sample preparation: The sides and back of the sample are sealed with corrosion-resistant sealant, leaving only the front coating exposed to simulate the corrosion surface of the wheel hub in actual service. Judgment rules: Open the box every 12 hours to visually observe the coating surface and record the time (in hours) when the coating first appears with rust spots or pitting. Acceptance criteria: the first pitting time is ≥1000 hours; if there is still no pitting after 1600 hours, terminate the test and record >1600 hours.

[0051] Table 1 Product Performance Test Results

[0052] As described in Examples 1 to 4, using a commercially available ordinary NiCr-Cr3C2 combined with a commercially available WC-10Co4Cr double-layer coating can achieve over 1000 hours of neutral salt spray without pitting corrosion. Increasing the surface layer thickness can slightly reduce erosion wear and extend the corrosion protection time. By modifying NiCr-Cr3C2 and introducing a Cr3C2@NiCr-Mo-La2O3-TiC transition strengthening layer, the residual thermal stress at the coating interface can be better reduced, and the crack resistance, erosion resistance, and corrosion resistance are significantly enhanced.

[0053] A comparison of Examples 1 and 4 with Comparative Examples 1 and 2 shows that when only a single-layer coating is set without a hard and wear-resistant WC surface layer, the amount of sand and gravel erosion wear increases significantly due to the lack of a high-hardness carbide wear-resistant skeleton support. Even when using Cr3C2@NiCr-Mo-La2O3-TiC modified powder to prepare a single layer, the erosion resistance is still much weaker than that of the double-layer composite system, proving that the combination of the transition layer and the surface layer has a synergistic gain in wear resistance and corrosion prevention, and both layers are indispensable.

[0054] The comparison between Example 4 and Comparative Example 3 shows that after removing La2O3, the system lacks the effects of rare earth grain refinement, melt pool purification and stress dispersion. The residual thermal stress at the coating interface increases significantly, network microcracks appear after thermal cycling, the amount of erosion wear doubles, and the neutral salt spray protection time is significantly shortened. This proves that La2O3 is a key functional component of the powder modification system and cannot be omitted.

[0055] As can be seen from the comparison between Example 4 and Comparative Examples 4 and 5, although replacing La2O3 with equal amounts of rare earth elements such as Y2O3 and CeO2 still provides the effects of grain refinement, density and corrosion protection, the overall performance of thermal stress suppression and long-term corrosion resistance is slightly lower than that of the La2O3 compound system. There is also a gap in the overall protection stability under high temperature and cold and hot cycling conditions, which proves that the synergistic effect of La2O3 with Mo and nano TiC is the best.

[0056] While the specific embodiments of the present invention have been described above, they are not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art without creative effort based on the technical solutions of the present invention are still within the scope of protection of the present invention.

Claims

1. A heavy-duty automobile wheel hub reinforced with a NiCr-Cr3C2 / WC-10Co4Cr composite coating, characterized in that, include: Heavy-duty car wheel hubs; The heavy-duty vehicle wheel hub surface has a multi-functional transition layer; The multifunctional transition layer is loaded with a surface layer; The material of the multifunctional transition layer is NiCr-Cr3C2 or Cr3C2@NiCr-Mo-La2O3-TiC; The surface layer is made of WC-10Co4Cr.

2. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 1, characterized in that, The coating thickness of the multifunctional transition layer is 10-12 mils.

3. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 1, characterized in that, The coating thickness of the surface layer is 3 to 5 microns.

4. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 1, characterized in that, The Cr3C2@NiCr-Mo-La2O3-TiC is composed of the following raw materials in weight percentages: Cr3C2: 68%–75%, NiCr: 22%–28%, Mo: 0.8%–2.5%, La2O3: 0.3%–1.2%, and TiC: 0.2%–0.8%.

5. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 1, characterized in that, The preparation method of Cr3C2@NiCr-Mo-La2O3-TiC includes: Cr3C2 was activated using a silane coupling agent; The activated Cr3C2, Ni, Cr, Mo, La2O3 and TiC are mixed, wet ball milled, spray granulated and vacuum sintered to obtain the final product.

6. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 5, characterized in that, The ball milling speed is 350-400 r / min, and the ball milling time is 4-6 h.

7. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 5, characterized in that, The vacuum sintering is carried out under inert gas protection, with the temperature raised to 950-1050℃ and held for 30-40 minutes.

8. The heavy-duty vehicle wheel hub reinforced with NiCr-Cr3C2 / WC-10Co4Cr composite coating as described in claim 1, characterized in that, The transition layer and top layer are applied using supersonic flame spraying.

9. The heavy-duty vehicle wheel hub prepared by the method according to any one of claims 1-8.

10. Application of NiCr-Cr3C2 / WC-10Co4Cr composite coating or Cr3C2@NiCr-Mo-La2O3-TiC / WC-10Co4Cr composite coating in the preparation of industrial heavy-duty casters, logistics equipment, engineering machinery and agricultural machinery.